Application of Baveno Criteria and Modified Baveno Criteria with Shear-wave Elastography in Compensated Advanced Chronic Liver Disease - Kang, Seong Hee; Baik, Soon Koo; Kim, Moon Young (Journal of Korean medical science, 2020)
We aimed to validate Baveno VI and expanded Baveno VI criteria using two dimensional shear-wave elastography (2D-SWE) in compensated advanced chronic liver disease (cACLD) patients with alcohol as the main etiology.BACKGROUNDWe aimed to validate Baveno VI and expanded Baveno VI criteria using two dimensional shear-wave elastography (2D-SWE) in compensated advanced chronic liver disease (cACLD) patients with alcohol as the main etiology.Clinical data from 305 patients with cACLD who underwent a liver stiffness measurement (LSM) with 2D-SWE and endoscopy were consecutively collected.METHODSClinical data from 305 patients with cACLD who underwent a liver stiffness measurement (LSM) with 2D-SWE and endoscopy were consecutively collected.Among 305 patients, high-risk varix (HRV) was identified in 21.3% (n = 65). The main etiology was alcoholic liver disease (51.8%), followed by hepatitis B virus (29.8%) and hepatitis C virus (9.1%). Baveno VI criteria spared endoscopy in 118 of the 305 (38.7%) patients, and 7 (5.9%) were missed with HRV. Expanded Baveno VI criteria spared more endoscopies (60.0%), but missed more HRV (9.8%) compared with Baveno VI criteria. The other classification described as the modified Baveno VI criteria were LSM < 25 kPa and PLT ≥ 150 × 10³/mm³. In total, 131 of the 305 (43.0%) patients were within the modified Baveno VI criteria, of whom seven (5.3%) had missed HRV. After adding spleen diameter < 12 cm to the modified Baveno VI criteria, the number of spared endoscopies increased by 106/305 (34.8%), with three (2.8%) presenting with HRV, indicating a risk of missing HRV.RESULTSAmong 305 patients, high-risk varix (HRV) was identified in 21.3% (n = 65). The main etiology was alcoholic liver disease (51.8%), followed by hepatitis B virus (29.8%) and hepatitis C virus (9.1%). Baveno VI criteria spared endoscopy in 118 of the 305 (38.7%) patients, and 7 (5.9%) were missed with HRV. Expanded Baveno VI criteria spared more endoscopies (60.0%), but missed more HRV (9.8%) compared with Baveno VI criteria. The other classification described as the modified Baveno VI criteria were LSM < 25 kPa and PLT ≥ 150 × 10³/mm³. In total, 131 of the 305 (43.0%) patients were within the modified Baveno VI criteria, of whom seven (5.3%) had missed HRV. After adding spleen diameter < 12 cm to the modified Baveno VI criteria, the number of spared endoscopies increased by 106/305 (34.8%), with three (2.8%) presenting with HRV, indicating a risk of missing HRV.Baveno VI and expanded Baveno VI criteria with 2D-SWE were insufficient with an HRV miss rate of over 5%. The modified Baveno VI criteria with spleen diameters < 12 cm with 2D-SWE spared more endoscopies with a minimal risk of missing HRV in cACLD patients with alcohol as the main etiology.CONCLUSIONBaveno VI and expanded Baveno VI criteria with 2D-SWE were insufficient with an HRV miss rate of over 5%. The modified Baveno VI criteria with spleen diameters < 12 cm with 2D-SWE spared more endoscopies with a minimal risk of missing HRV in cACLD patients with alcohol as the main etiology.